#makiBaka "pag panikas sa karne, undanga kini:" : a communication campaign plan to raise awareness on adulterated meat and food animal flooding - Algones, Ela-Christian B. (2019)
The main purpose of this study is to design a communication campaign plan for the Tagum City Veterinarian Office (CVO) to address the lack of communication intervention regarding the issue of adulterated meat and food animal flooding. This issue is both a form of animal cruelty and consumer rights violation. The study is a mixed method study: (1) Quantitative part: a self-administered questionnaire was distributed among the residents of Visayan Village Tagum City to identify their level of knowledge, attitude, and belief regarding the issue and their willingness to cease patronizing such meat. (2) Qualitative part: the researcher interviewed several government agencies that are connected to this issue. To analyse the quantitative data, the researcher utilized the Spearman Rho and Chi-square. For the qualitative data, thematic analysis was used. Results show that majority of the residents have an average level of knowledge regarding the issues. The same goes with their attitude, belief, and intention. Majority of the respondents care about the issue and sees it as something that is not normal and are willing to stop patronizing adulterated meat. The campaign design focuses on increasing level of knowledge regarding the issue of adulterated meat and food animal flooding and reinforces the current attitude, beliefs, and intention that the residents have. The message design and execution are age-appropriate, relevant, easy to comprehend, and religiously appropriate as per the results of the study implied. The execution utilized are: infographics, press releases, live radio interviews, web series, radio commentary, and seminars/training. Communication medium utilized are: Facebook, Radio, and On-ground activation. This campaign is set to run for 6 months starting on the 1st day of UGMAD celebration (September 1) ? February 25. To analyse the results of the campaign, two methods will be utilized. For the quantitative: (1) Social Media Analysis. (2) Advertising Value equivalency, and (3) Attendance report during Training and Seminars. While for the qualitative, thematic analysis will be utilized. It is also advised that the questionnaire used in this study will be re-distributed to test whether there is a difference between the new and old data.